Estimation of carbon stocks in harvested wood products of buildings in Japan: flux-data method and direct inventory method - Ryoto Matsumoto; Chihiro Kayo (Journal of Wood Science, 2022)
Abstract In this study, carbon stocks in harvested wood products (HWPs) of buildings in Japan were estimated using the direct inventory method, which is highly accurate, and the flux-data method, which was proposed by the Intergovernmental Panel on Climate Change (IPCC) and is commonly used worldwide. We analyzed the differences between the estimated results and the respective reasons. The results indicate that the flux-data method greatly underestimated the carbon stocks in HWPs of buildings in Japan. In 2019, the values estimated by the flux-data method were only approximately 64% of those estimated by the direct inventory method. The half-lives of HWPs and the estimated continuous rate of change in industrial roundwood consumption proposed by the IPCC were likely the main causes of this difference. As for the decay function, the first-order decay, which is a default function proposed by the IPCC, was considered reliable for the estimations, because the decay function was not the main cause of the obtained difference.